Broken Bodies, Healed Body: Contemporary Martyrdom and Ecumenism - Nguyen, Peter, SJ (Journal of religion & society. Supplement, 2019)
I demonstrate that contemporary martyrdom is a form of ecumenism because it is a dialogue amongst Christians from different backgrounds, founded on fidelity to the ultimate religious truth – the sovereignty of Jesus Christ. The most striking form of ecumenism is that of the martyrs who reveal the truth of all humanity’s communion with Christ. This paper involves four steps. The first part acknowledges the scandal of early modern Christians making martyrs of one another which helped to divide the Christian body. The second demonstrates, according to John Paul II, that the martyrs of the twentieth century have contributed to the ecumenical movement. The third analyzes the shared martyrdom between the German Jesuit Alfred Delp and the Lutheran Helmuth James von Moltke, executed for being members of an anti-Nazi resistance group. The fourth concludes that these martyrs witnessed the truth of Christ, who is the universal truth that links another with oneself in a shared humanity.